WALHI DAN #SAVEMERATUS (MOBILISASI SUMBERDAYA GERAKAN SOSIAL) - Azmi Riyadi; Dimas Asto Aji An'Amta (Multikultural: Jurnal Ilmu Sosial, 2023)
The #SaveMeratus movement is an environmental initiative aimed at protecting the Meratus Mountains from harmful exploitation and preserving all aspects within it. The movement involves various efforts, such as protest demonstrations, petition gathering, online campaigns, and legal actions. One organization contributing to this movement is Walhi Kalsel, actively participating in activities related to the #SaveMeratus cause. The key factor in this movement is resource mobilization, and this research aims to describe how Walhi Kalsel mobilizes resources in its contribution to the #SaveMeratus movement. The theoretical framework employed is resource mobilization theory. This study adopts a qualitative-descriptive method and a case study approach. The findings reveal significant factors supporting the #SaveMeratus movement. In the context of social movement organizations, Walhi Kalsel aligns its values and principles with the struggle to #SaveMeratus. Leadership plays a crucial role, and Walhi Kalsel's leaders actively engage in the #SaveMeratus movement. Additionally, Walhi Kalsel successfully mobilizes various resources, including moral, cultural, human, organizational-social, and material resources to support the #SaveMeratus movement.